Plasma Pressure Distribution in the Surrounding the Earth Plasma Ring and Its Role in the Magnetospheric Dynamics - Stepanova, M (Elsevier Ltd, 2014)
We analyzed the characteristics of the plasma region surrounding the Earth at the geocentric distances between 6 and 15RE using the data of THEMIS mission from April 2007 to September 2012. The obtained averaged distributions of plasma pressure, of pressure anisotropy, and of magnetic field near the equatorial plane showed the presence of a ring-shaped structure surrounding the Earth. It was found that for quiet geomagnetic conditions the plasma pressure is nearly isotropic for all magnetic local times at geocentric distances >6RE. Taking into consideration that the minimal values of the magnetic field at the field lines near noon are shifted from the equatorial plane, we estimate the value of plasma beta parameter in the region of minimal values of the magnetic field using the Tsyganenko-2001 magnetic field model. It was found that the values of plasma beta parameter are of the order of unity for the nightside part of the ring-shaped structure in the equatorial plane and for the region of minimal values of the magnetic field in the dayside, indicating that the ring-shaped structure should play an active role in the magnetic field distortion. Comparison of obtained distribution of plasma pressure at the equatorial plane with the values of plasma pressure at low altitudes, showed that the considerable part of the auroral oval can be mapped into the analyzed plasma ring. The role of the high-beta plasma ring surrounding the Earth for Earth-Sun System disturbances is discussed. © 2013 Elsevier Ltd.